DEZ ANOS DA ABRALIC (1986 - 1996): ELEMENTOS PARA SUA HISTÓRIA - Carvalhal, Tania Franco (Organon, 2012)
1985. Antonio Candido was appointed for the Executive Committeeof the International Comparative Literature Association (ICLA), during theXI Conference, in Paris. One year after the XI Congress, Porto Alegre,favoured by its geographic location, and natural bilinguism andmulticulturalism, becomes the site for the Comparative Literature BrazilianAssociation, ABRALIC. The Latin-American participation and perspectivewere the central themes of the I Seminar, which was fully succesful in itsproposes. Three congresses were held ever since and in August 1992, ICLAgathered together for the first time in Latin America, precisely at the FederalUniversity of Rio Grande do Sul. The success of the Brazilian initiative iscomplete and the creation of several graduated courses and otherinstitutions, similar to ABRALIC, in the neighbouring countries give evidenceof that.